(3CVhGA Ydi GdLgGR GdEOGQj GdYQHj (B:s (3GdJfXje heSejGJ GdhXGFa hGdCLhQ (B/s - (3agej, LdGd GdOjf eMeOs ((3GdbGgQI(B: s (3GdefXeI GdYQHjI ddJfejI GdEOGQjI(B, s, 2005)
(3GdJfXje GdEOGQj GdQSej ddOhdI, GdgjGcd GdJXjejI dhMOGJ GdLgGR GdEOGQj HGdOhdI, GdJUfja GdfeWj hZjQ GdfeWj deSejGJ GdhXGFa HGdLgGR GdEOGQj GdYQHj, GdCLhQs
(3HHdjhZQGajG(B: (3U(B.155s
Keywords: (3GdEOGQI GdYGeIs; (3JfXje hEOGQIs